Kontribusi Pendapatan Pembuat VCO (Virgin Coconut Oil) pada KWT Bina Amerta terhadap Pendapatan Rumah Tangga di Kabupaten Jembrana Bali - MAHAYANI, KOMANG IRA; DARMAWAN, DWI PUTRA; SUSRUSA, KETUT BUDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p30, 2023)
Income Contribution of VCO (Virgin Coconut Oil) Makers at KWT Bina Amerta to Household Income in Jembrana Regency, Bali   The role and position of women in society begins with their position in the household, namely as a wife and housewife. But now a woman has started to participate in economic activities. The economic activity of the community that cannot be separated from the involvement of women is in the agricultural sector. Various productive activities in the agricultural sector began to be carried out by individuals and organizations such as the Women Farmers Group (KWT). One form of productive activity that has been carried out by KWT Bina Amerta in Jembrana Regency as an effort to utilize agricultural products and at the same time provide additional income is processing coconut into VCO. The large number of coconut plantations around the Bina Amerta KWT location is one of the reasons for the development of VCO processing. The research objectives are: 1) to analyze the income of KWT members who produce VCO in KWT Bina Amerta and 2) analyze the income contribution of KWT members who produce VCO at KWT Bina Amerta to household income. This study uses quantitative analysis methods. The sample used is KWT Bina Amerta members who are involved in VCO processing activities, namely 5 people. The results showed that: 1) the amount of net income earned by KWT members from VCO processing activities was IDR 40,000/day where in one month they usually produce for 15 days and in one year only produce effectively for 6 months so that the income earned by members is large. KWT from VCO processing activities for one year is IDR 3,600,000, 2) the income contribution of KWT members who produce VCO in KWT Bina Amerta to household income is 9%, which means the contribution given is still very low.